Seven new species of the genus Lathrobium Gravenhorst (Coleoptera: Staphylinidae: Paederinae) from Central Honshu, Japan, with new distributional records - Senda, Yoshihiro (Zootaxa, 2024)
Seven new apterous Lathrobium Gravenhorst species are described from Central Honshu, Japan, as follows (type locality of each species in parenthesis): L. oopikkarianum sp. nov. (Mt. Ôpikkari-yama, Shizuoka Pref.), L. elongatiphallus sp. nov. (Dando-uradani, Shitara-chô, Aichi Pref.), L. tomohidei sp. nov. (Tominaga, Toyota-shi, Aichi Pref.), L. pegaseion sp. nov. (Togakushi, Nagano Pref.), L. minoccidentale sp. nov. (Neomidori, Motosu-shi, Gifu Pref.), L. kawamurai sp. nov. (Neomidori, Motosu-shi, Gifu Pref.) and L. volkeri (Mt. Sanage-yama, Aichi Pref.). They are illustrated with the photographs of taxonomically important characters are provided. The endophallus of aedeagus and detail structure of female terminalia of L. satoi Watanabe, 2003 are described and illustrated for the first time based on the specimens collected from its type locality. Additional records of following species are reported: L. guts Senda, 2022, L. satoi Watanabe, 2003, L. kurosawai Watanabe, 2001, L. nabetaniense Watanabe, 1997, L. shiritakanum Watanabe, 1997 and L. shinanense Watanabe, 2011. An updated checklist of Japanese Lathrobium species is compiled.